HUBUNGAN PERILAKU MASYARAKAT EKONOMI RENDAH DESA KLENG COT AROEN DENGAN PENYAKIT GINGIVITIS - Cut Ratna Keumala (Jurnal Kesehatan Gigi, 2020)
Socio-economic status (SES) is related to one or more inhibiting factors taken into account for dental hygiene. Prevention of dental and oral diseases at low socioeconomic status has a lower level of prevention compared to that of dental and oral diseases prevention at relatively high socioeconomic status. The results of the preliminary examination in low economic families in 12 people shows that there were 6 people who experienced gingivitis. The purpose of this study is to determine the relationship of low economic society behavior with gingivitis in Kleng Cot Aroen, Baitusalam, Aceh Besar Regency in 2019. The population in this study was all low economic society in 55 families. The sample in this study used purposive sampling with the characteristics of people who were willing to be the sample, to collaborate and in the category of low economic society. The results show that there is a relationship between knowledge of low economic society behavior with gingivitis due to p-value of 0.000. In addition, there is a relationship between low economic society action to gingivitis due to p-value of 0.002, and there is a relationship between low economic society action to gingivitis with p-value of 0.000. In conclusion, there is a relationship between low economic society behavior with gingivitis, so it is suggested to those affected by gingivitis to maintain dental and oral hygiene by periodically checking dental and oral health and brushing it 2 times a day as well as checking into dental poly once six months.